Kritik Sosial Puisi â€œNegeri Sempurnaâ€ dan â€œNegeri Kadalâ€ pada Antologi Puisi Sajak Hoax Karya Sosiawan Leak - Kusuma, Indah Mauli; Nazurty, Nazurty; Nurfadilah, Nurfadilah (Jurnal Ilmiah Dikdaya, 2024)
The aim of this research is to determine the social criticism contained in the poems "Personal State" and "Negeri Kadal" by Sosiawan Leak. The research uses a qualitative approach method. The data in this research are words, lines and stanzas which contain a form of social criticism in poetry. The data source for this research was obtained from the poetry anthology book Sajak Hoax by Sosiawan leak. Data collection techniques in this research used reading, listening and note-taking techniques. Test the validity of this research data using theoretical triangulation techniques. The data analysis technique is to carry out in-depth reading until research results are obtained. Based on the analysis and discussion carried out by researchers, it can be concluded that the poems entitled The Perfect Country and the Lizard Country describe social criticism of political problems. The social criticism of political problems contained in the poem describes social criticism of various political problems that have occurred from the past to the present. Such as corruption, authoritarian power, social injustice, and manipulation of information in the political realm. Through his poetry, Sosiawan Leak also positions himself as a citizen who criticizes government policies and arbitrariness.